The palimpsest catena of Codex Zacynthius: text and translation - Houghton, H. A. G.; Manafis, Panagiotis; Myshrall, Amy (Texts and studies, 2021)
Frontmatter -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- Plates -- Edition -- Part I -- Part II -- Part III -- Appendix 1. Concordance of Undertext and Overtext Pages -- Appendix 2. List of Scholia -- Bibliography -- Index of Biblical Passages -- Index of Names